Scheme for the Development of Sharia-Compliant Financial Inclusion for Farmers on Dryland Area through the Optimization of Biological Assets - Rakhman, Kartika Nur; Fatwa, Nur (UI Scholars Hub, 2024)
Farmers in the Gunungkidul Regency are mostly categorized as impoverished. Resource constraints make it challenging for them to progress. One of the problems they face is the lack of capital for their businesses and daily needs. To meet these needs, they often resort to borrowing from loan sharks. This occurs partly due to the absence of assets they can use to access financing from Sharia-compliant financial institutions. This research aimed to assess the feasibility of biological assets, particularly teak trees (Tectona grandis), to be accepted as collateral in Sharia-compliant financing. Additionally, this study aimed to provide an alternative for developing Sharia-compliant financial inclusion in Indonesia. The research employed financial inclusion theory and biological asset appraisal methods using the IRR and NPV formulas. The IRR and NPV calculations revealed that biological assets, such as teak trees, can serve as an alternative for promoting Sharia-compliant financial inclusion in the Gunungkidul regency. Moreover, teak trees are suitable collateral for farmers seeking financing from Sharia-compliant financial institutions. The research results indicated that teak trees can be incorporated into Sharia-compliant financing schemes, such as Rahn and Mudarabah. This study is expected to enhance Sharia-compliant financial inclusion, as, until now, Sharia-compliant financial institutions have not included the potential of biological assets, particularly teak trees, as acceptable collateral in their financing practices.